Pharmacological Findings on the Biochemical Bases of Memory Processes: A General View - Iván Izquierdo; Martín Cammarota; Jorge H. Medina; Lia R. M. Bevilaqua (Neural Plasticity)
We have advanced considerably in the past 2 to 3 years in understanding the molecular mechanisms of consolidation, retrieval, and extinction of memories, particularly of fear memory. This advance was mainly due to pharmacological studies in many laboratories using localized brain injections of molecularly specific substances. One area in which significant advances have been made is in understanding that many different brain structures are involved in different memories, and that often several brain regions are involved in processing the same memory. These regions can cooperate or compete with each other, depending on circumstances that are beginning to be identified quite clearly. Another aspect in which major advances were made was retrieval and post-retrieval events, especially extinction, pointing to new therapeutic approaches to fearmotivated mental disorders.